ANALISIS NILAI-NILAI KARAKTER PADA FILM KARTUN THE SPONGEBOB MOVIE - Noorma Firman Zuhdi; Eka Sari Setianingsih; Asep Ardiyanto (Program Studi Pendidikan Guru Sekolah Dasar, Universitas PGRI Semarang, 2023)
This research is motivated by the lack of educating films for elementary school age children which can lead to a decline in children's morale so that character education is needed. Character education is needed to equip children to face social life in order to become human beings with morals. Character education in elementary school children can be taught through film shows, but still under the supervision of parents and teachers. This research is focused on examining eighteen character values according to the 2010 Ministry of National Education, such as Religious, Honest, Tolerance, Discipline, Hard Work, Creative, Independent, Democratic, Curiosity, National Spirit, Love of the Homeland, Appreciating Achievement, Friendly/Communicative, Love of Peace. , Love to read, Care for the environment, Social care, and Responsibility, which are contained in the animated film The Spongebob Movie 2020. The type of research used is qualitative research. The purpose of using qualitative methods is to obtain in-depth data. Data obtained through observation, documentation, and note-taking methods. From the research conducted, the results obtained are that the animated film The Spongebob Movie 2020 has character values of honest, hard work, creative, democratic, curiosity, love for the homeland, respect for achievement, friendly, love peace, love to read, care for the environment, care social, and responsibility. The thirteen character values appear in each scene with a reference to eighteen character values according to the 2010 Ministry of National Education, therefore this film can be used as a vehicle for character education for elementary school students in the learning process.